The influence of interpersonal communication and school climate on state elementary school teachers’ performance - Nursida; Kadri , Hanif Al; Rusdinal; Syahril (Indonesian Research Journal in Education |IRJE|, 2025)
This research aimed to reveal the influence of interpersonal communication and school climate on teacher performance. This research employed a quantitative correlational design of an associative type. The population in this research consisted of all teachers with civil servant (ASN) status at elementary schools in Sungai Aur District, totaling 219 teachers from 20 elementary schools. The sample was determined using the Cochran formula. The sampling technique used was proportionally stratified random sampling. The research instrument used a Likert scale questionnaire with five alternative answers. The data analysis technique was done using multiple linear regression tests processed using SPSS version 25. The results of the research data analysis indicated that 1) interpersonal communication influenced teacher performance by 73.6%, 2) school climate influenced teacher performance by 74.2%, and 3) interpersonal communication and school climate influenced teacher performance by 79.3%.